PELAKSANAAN KEBIJAKAN PEMERINTAH DAERAH TERHADAP PENCAPAIAN TARGET PENERIMAAN PAJAK HOTEL PADA PEMERINTAH KABUPATEN SUKABUMI - Aldi Septian Pujantara (Jurnal Akuntansi UMMI, 2020)
This research is aimed at recognizing the significant amount of Hotel Tax revenue in Sukabumi Regency from year to year. The independent variable in this study is the Implementation of Local Government Policy and the dependent variable in this study is the Achievement of the Hotel Tax Targets. The method used in this research is descriptive, associative method with the type of survey research on secondary data. Descriptive method used to test the hypotheses proposed by using statistical techniques and then drawn conclusions. While time series data or also called time series data is a collection of data from a particular phenomenon obtained in certain time intervals, for example in the weekly, monthly, or yearly period. the implementers in applying the work in the field and the program policies that have been clearly established are easy to understand but sometimes less understood by the implementers of the policy itself when applying it in the field so that the policy implementers sometimes in carrying out their duties are not in accordance with the SOPs that have been made making it difficult to work in the field . The achievement of the Hotel Tax revenue target in Sukabumi Regency has already reached the target set, sometimes more than what is targeted is seen from the 2013 hotel tax revenue target increased 87%. In 2014 and in 2015 the target of hotel tax revenue increased by 77.66%. The target of hotel tax revenue from year to year continues to experience a significant increase with an average growth of 82.66% although in percentage the growth of the revenue target has decreased between 2013 to 2014 with 2014 to 2015 by 10%, this due to the influence of other factors. As the full influence of the implementation of the policy based on the conditions of policy implementation, the Hotel Tax revenue has reached the target set by the Government of Sukabumi Regency